Cervical Auscultation Machine Learning for Dysphagia Assessment - Chia, An An; Lum, Stacy; Boo, Michelle; Tan, Rex; B.T, Balamurali; Chen, Jer-Ming (International Conference on Signal Processing and Communications, 2024)
This study evaluates the use of machine learning, specifically the Random Forest Classifier, to differentiate normal and pathological swallowing sounds. Employing a commercially available wearable stethoscope, we recorded swallows from both healthy adults and patients with dysphagia. The analysis revealed statistically significant differences in acoustic features, such as spectral crest, and zero-crossing rate between normal and pathological swallows, while no discriminating differences were demonstrated between different fluid and diet consistencies. The system demonstrated fair sensitivity (mean ± SD: 74% ± 8%) and specificity (89% ± 6%) for dysphagic swallows. The model attained an overall accuracy of 83% ± 3%, and F1 score of 78% ± 5%. These results demonstrate that machine learning can be a valuable tool in non-invasive dysphagia assessment, although challenges such as sampling rate limitations and variability in sensitivity and specificity in discriminating between normal and pathological sounds are noted. The study underscores the need for further research to optimize these techniques for clinical use.